Vibration Analysis of Plate with Irregular Cracks by Differential Quadrature Finite Element Method - Zhongyuan Xu; Wei Chen (Shock and Vibration)
A universal method combining the differential quadrature finite element method with the virtual spring technique for analyzing the free vibration of thin plate with irregular cracks is proposed. Translational and rotational springs are introduced to restrain the vertical displacement and orientation of the plate. The mass matrix and stiffness matrix for each element are deduced involving the effects of the virtual springs. The connection relationships between elements can be modified by setting the stiffness of the virtual springs. The vibration of two rectangular plates with three irregular shaped cracks and different boundary conditions are presented. The results are compared with those obtained by ANSYS, where the good agreement between the results validates the accuracy and efficiency of the present method.